The term structure, leading indicators, and recessions: Evidence from Switzerland, 1974-2017 - Rebecca Stuart (Swiss Journal of Economics and Statistics, 2020)
This paper studies the predictive power for recessions of the slope of the Swiss term structure using monthly data for 1974-2017. Dynamic probit models indicate that the term structure contains information useful for predicting recessions for horizons up to 19 months. Whether the economy is currently in recession or not is also useful for forecasting recessions. These relationships prove stable over the sample. Robustness tests indicate that the KOF business course indicator and some monetary aggregates contain different information from the term structure which can improve the in- and out-of-sample fit of the model.
Keywords: C25; E00; E43; 330; Switzerland; Term structure; Recessions; Leading indicators